Sustainable development of protein-fortified Quince (Cydonia oblonga) fruit leather using almond powder: Nutritional quality, antioxidant capacity, and tensile strength - Nagina Batool; Zunaira Arshad; Nabeel Ashraf; Farah Jameel; Rola A. Jalloun; Alanood A. Alfaleh; Duaa Altuwairki; Abeer A. Aljehani; Mahmoud Helal; Awatif Almehmadi; Rokayya Sami (PLoS ONE, 2026)
Fruit leathers are delicious, convenient and shelf-stable alternative of fresh fruits offering benefits of valuable sources of nutrients, dietary fiber and bioactive compounds. The novelty of almond-fortified quince fruit leather lies in combining quince’s natural antioxidants and dietary fiber with the protein and healthy nutrients of almonds to produce nutritionally enriched, plant-based snack. This fortification improves the nutritional and functional value compared to conventional carbohydrate-rich fruit leathers. This research was done to assess the impact of adding almond powder as a protein fortifier in the quince fruit leather. Fruit leather samples were prepared by hot air drying at 65 °C for 8–12 hours. There were five formulations (T 0 ; control; 100% quince pulp), T 1 (95% quince pulp + 5% almond powder), T 2 (90% quince pulp + 10% almond powder), T 3 (85% quince pulp + 15% almond powder) and T 4 (80% quince pulp + 20% almond powder). The moisture content and nitrogen-free extract (NFE) reduced significantly among treatments (T 0 -T 4 ) with values of 23.22% −11.24% and 66.96% −15.79%, respectively. While, fat, fiber, protein and ash contents were significantly increased all over the treatments, with values recorded at T 0 -T 4 (6.60%−33.32%), (17.30%−32.72%), (0.63%−9.18%), and (3.53%−13.19%), respectively. The total phenolic content (TPC), total flavonoid content (TFC), and DPPH radical scavenging activity were also increased significantly and ranged between 164.75 to 170.32 mg GAE/g, 82.91 to 90.38 mg QE/g and 58.29 to 71.53 mg TE/g in T 0 and T 4 , respectively. Water and oil absorption rates were reduced (T 0 -T 4 ) from 2.17 to 2.12 mg/g and 2.20 to 0.60 mg/g, respectively. The amount of vitamin C dropped considerably in T 0 (17.43 mg/100g) to T 4 (7.67 mg/100g), respectively. The addition of almond powder significantly affected the texture of quince fruit leather, with tensile strength decreasing from 1.46 MPa (T 0 ) to 0.04 MPa (T 4 ), elongation from 15.66% to 1.07%, and rupture strength from 64.93 N to 22.88 N, reflecting disruption of the pectin network and increased porosity caused by dispersed almond particles. Browning index rose substantially when almond powder is added, and it varies between 33.12 and 51.19 among T 0 -T 4 samples. This study indicated that the T 2 showed the best results and demonstrated high nutritional and tensile strength. This fruit leather could potentially be regarded as a high-nutrient, healthy and convenient alternative snack food.